Metode Dakwah Majelis Pengkajian Tauhid Tasawuf Pada Masyarakat Desa Likupang Dua Provinsi Sulawesi Utara - Aditya Engelen; Mustafa Mustafa; Musafar Musafar (Ahsan: Jurnal Dakwah dan Komunikasi, 2022)
The Research Council for Tawhid Sufism in the Likupang Dua Community was initiated in its development by receiving enthusiasm and support from members at the provincial, national, and even international levels. The Tauhid Tasawuf Study Council is an Islamic organizational institution that invites people to worship with complete devotion and good morals; the focus in discussing this journal article is the Method of Da'wah Study of the Tauhid Sufism Study Council to the Likupang Dua Community and the implications for the community around Likupang Dua. Using a qualitative descriptive approach method. Collecting data using observation, interviews, and documentation. The results of this study indicate that the da'wah method carried out by MPTT to the Likupang Dua community is by carrying out muzakarah Tauhid Sufism, remembrance and ratib siribe, reciting from door to door and fardiyah da'wah methods, then the polemic implications for the surrounding community who agree and some who still do not accept the da'wah method from MPTT because it was considered to have other interests still. Keywords : Da’wah Methods, Tawhid Sufism, Study Council Sufism